MEMENTO MORI: EXISTENTIAL AND RELIGIOUS PERSPECTIVES ON DEATH - Subhan, Arief (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Death is often understood as the antithesis of life, with ideas of our impermanence coming in diverse forms. The existentialists would argue that existence precedes essence; therefore, meaning is created, with both life and death conceptualized in accordance with the conscious self. For the believer in God, s/he would argue that essence precedes existence, implying that meaning is there for us to grasp and to embrace, both in this world and the assumed next. Such an 'essence' is one which pertains to divinity and its contingent awareness as well as expression. This article compares the ideas of death brought forward by existentialists with those elucidated by religionists. For the former, we shall engage with the French-Algerian philosopher Albert Camus and his notion of Absurdism. For the latter, we shall delve into the work of Titus Burckhardt, who touched upon concepts like annihilation of individuality (fana’) and a subsisting in/with the divine. Aiming to express this perennial subject's depth, examples from other faith systems will also be gleaned. We are not attempting a synthesis of the two frameworks; rather, we intend to draw attention to a shared human condition and its diverse views on death.